Enhancing Election Oversight: Addressing Human Resource and Infrastructure Challenges in Bawaslu Boalemo Regency - A. Djakaria, Rahmat; Ariawan, Ariawan; Mustafa, Muh. Sabir (International Journal of Multidisciplinary Approach Research and Science, 2025)
Human resource (HR) management plays a crucial role in the effectiveness of election supervisory bodies, particularly in resource-constrained settings. This study explores the challenges faced by the Election Supervisory Body (Bawaslu) in Boalemo Regency during the 2024 elections. Using a qualitative approach, the research examines the impact of staffing shortages, inadequate training, facility constraints, and ineffective management practices on operational performance. The findings highlight that overlapping responsibilities, outdated infrastructure, and a lack of structured management frameworks significantly hinder the organization's ability to execute its mandate. Targeted interventions, including capacity building, technology adoption, and leadership development, are identified as critical solutions. The study concludes that addressing these issues through strategic HR practices and infrastructure enhancements can improve operational efficiency and ensure electoral integrity. These insights offer valuable guidance for policymakers and practitioners aiming to strengthen public sector performance in similar contexts.